Qualitative, Quantitative, and Integrative Conservation - Jamison E. Colburn (Washington University Journal of Law & Policy, 2010)
Professor James E. Colburn's article illustrates the barriers to carrying biodiversity conservation into the twenty-first century. His probing article demonstrates the truth of the first book of Genesis, that new knowledge can be a mixed blessing. Using as examples the critical habitat designation for the Canadian Lynx and the listing of the Polar Bear as a threatened species, Professor Colburn argues that we lack the institutional capacity to apply scientific advances when making conservation decisions. The tragedy of modern biology is that the more risk information we have (and are required to try and assemble), "the less certain we are that we can ever know which biological entities merit our protection." Professor Colburn's article identifies three tensions that impede current efforts to protected threatened and endangered species. First, biodiversity conservation is becoming just another risk management problem which requires dynamic decision-making under varying conditions of uncertainty; put differently, it is an example of the theoretical convergence now taking place in environmental law. Biodiversity conservation is moving toward the toxics regulation model with, as Professor Adelman's article in this symposium so well enumerates, all the problems of this project. Second, post-Chevron administrative law often subjects agency decisions to unpredictable judicial review; and third, we are seriously under-investing in biodiversity conservation, which results in internal regulatory gridlock. "The ESA saddles the Services with far too many conjunctive tasks today, inviting their opponents to disrupt, delay, and defeat them." To correct this situation, Professor Colburn proposes what amounts to a "regulatory science" solution. Ultimately the ocean of available data must be shaped and adapted to the cognitive capacity of the users to provide managerial benchmarks to evaluate, inter alia, habitat designation; human, biological, and chemical interactions of the "whole 'earth system;'" and the "evolutionary processes of speciation."
Keywords: Environmental law; Environmental protection; Ecological disturbances; United States. Endangered Species Act of 1973; Biodiversity conservation; Wildlife conservation